2010
DOI: 10.3238/arztebl.2010.0457
|View full text |Cite
|
Sign up to set email alerts
|

Salt Restriction for the Prevention of Cardiovascular Disease

Abstract: On the basis of the available studies, it seems likely that a moderate lowering of the daily intake of sodium chloride by the general population from 8 to 12 grams per day (the current value) to 5 to 6 grams per day would be a useful public health measure, with economic benefits as well. The potential risks for certain groups of individuals are foreseeable and controllable. A general reduction of dietary salt intake can only be achieved by reducing the sodium chloride content of industrially processed foods, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 66 publications
2
12
0
4
Order By: Relevance
“…As current data reveal an average daily consumption of 3 to 6 g of sodium, corresponding to 7.5 to 15.0 g of salt across populations [99], mostly assigned to the use of processed foods [52], recent global and American guidelines on cardiovascular disease prevention recommend a maximum daily sodium intake of 1.5 to 2.4 g (3.75 to 6.0 g of salt) [34,41,58]. A daily salt restriction to 5-6 g is also recommended by the European Society of Hypertension (ESH) and the European Society of Cardiology (ESC) [71].…”
Section: Salt-induced Cardiovascular Morbidity and Mortalitymentioning
confidence: 98%
“…As current data reveal an average daily consumption of 3 to 6 g of sodium, corresponding to 7.5 to 15.0 g of salt across populations [99], mostly assigned to the use of processed foods [52], recent global and American guidelines on cardiovascular disease prevention recommend a maximum daily sodium intake of 1.5 to 2.4 g (3.75 to 6.0 g of salt) [34,41,58]. A daily salt restriction to 5-6 g is also recommended by the European Society of Hypertension (ESH) and the European Society of Cardiology (ESC) [71].…”
Section: Salt-induced Cardiovascular Morbidity and Mortalitymentioning
confidence: 98%
“…In the recently published systematic review and meta-analysis of prospective studies published by Strazzullo et al in 2009 [11], including 19 independent cohort samples with more than 170 000 participants and a follow-up between 3.5 and 19 years, higher salt intake was associated with a significantly greater risk of stroke (pooled relative risk 1.23; 95% confidence interval 1.06-1.43; P ¼ 0.007) and a tendentially higher, though nonsignificant, risk of cardiovascular disease was observed (pooled relative risk 1.14, 95% confidence interval 0.99-1.32; P ¼ 0.07). In a recently published narrative review, multiple studies have shown that the adjusted relative risk reduction in controlled observational studies aiming for reduced sodium intake ranged from 25% over 15 years to 41% over 3 years [45]. The effect of a direct application of a salt reduction in daily life has been demonstrated in an RCT, which investigated the Dietary Approaches for Stop Hypertension (DASH) diet, rich in fruits and vegetables and low-fat diary products in combination with reduced dietary sodium uptake.…”
Section: Discussionmentioning
confidence: 98%
“…The Swedish Obese Subject Study (SOS) in which more than 1700 patients successfully reduced their body weight by means of bariatric surgery has shown that the initial postsurgical blood pressure reduction was still present after 2 years, but was almost gone 10 years later [50]. In terms of adverse events, Klaus et al [45] gave an overview on possible risks in terms of a dietary salt reduction, suggesting that with a modest dietary salt restriction to 5-6 g/day, short episodes of severe diarrhea or longer episodes of vomiting are not likely to cause sodium deficiency. Even in geriatric patients and pregnant women, Klaus et al [45] deem the benefit as exceeding potential harm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…He et al 33 reported an association between soda consumption and increased sodium intake in this age group. Guidelines to restrict sodium intake are among the most important measures for primary prevention of cardiovascular disease 34 .…”
Section: Discussionmentioning
confidence: 99%